Association between sarcopenia and respiratory function in elderly orthopedic outpatients. Issue 29 (22nd July 2022) - Tomita, Yoshihito; Mizukami, Satoshi; Nishimura, Takayuki; Arima, Kazuhiko; Abe, Yasuyo; Kanagae, Mitsuo; Aoyagi, Kiyoshi
Abstract : The relationship between sarcopenia and respiratory function has not been investigated in elderly Japanese orthopedic outpatients. This study aimed to assess the relationship between sarcopenia and respiratory function in elderly orthopedic outpatients in Japan. Elderly outpatients (n = 102; aged ≥65 years) with orthopedic diseases were enrolled in the study. Muscle mass was measured using the bioelectrical impedance analysis. Grip strength and walking speed were measured (2 trials). The respiratory function (e.g., percent vital capacity [VC] and percent forced expiratory volume in 1 second) was also measured. The association between sarcopenia and respiratory function was assessed using logistic regression analysis, adjusting for sex, comorbidities, and smoking status. The mean ages for men and women were 77.7 ± 8.3 and 76.5 ± 6.8 years, respectively, and the overall prevalence of sarcopenia was 25.5% (30.0% and 24.4% in men and women, respectively). The study demonstrated that low respiratory function, which was represented by decreased percent VC, was associated with sarcopenia in outpatients visiting an orthopedic department (odds ratio, 1.73; 95% confidence interval: 1.02–2.97). Sarcopenia was significantly associated with a lower percentage of VC in orthopedic outpatients after adjustment for sex, comorbidity, and smoking. Further studies are needed to determine the causality.